Tetranorsesquiterpenoids as Attractants of Yucca Moths to Yucca Flowers. - Tröger, Armin; Svensson, Glenn P; Galbrecht, Hans-Martin; Twele, Robert; Patt, Joseph M; Bartram, Stefan; Zarbin, Paulo H G; Segraves, Kari A; Althoff, David M; Von Reuss, Stephan; Raguso, Robert A; Francke, Wittko (My University, 2021)
The obligate pollination mutualism between Yucca and yucca moths is a classical example of coevolution. Oviposition and active pollination by female yucca moths occur at night when Yucca flowers are open and strongly scented. Thus, floral volatiles have been suggested as key sensory signals attracting yucca moths to their host plants, but no bioactive compounds have yet been identified. In this study, we showed that both sexes of the pollinator moth Tegeticula yuccasella are attracted to the floral scent of the host Yucca filamentosa. Chemical analysis of the floral headspace from six Yucca species in sections Chaenocarpa and Sarcocarpa revealed a set of novel tetranorsesquiterpenoids putatively derived from (E)-4,8-dimethyl-1,3,7-nonatriene. Their structure elucidation was accomplished by NMR analysis of the crude floral scent sample of Yucca treculeana along with GC/MS analysis and confirmed by total synthesis. Since all these volatiles are included in the floral scent of Y. filamentosa, which has been an important model species for understanding the pollination mutualism, we name these compounds filamentolide, filamentol, filamental, and filamentone. Several of these compounds elicited antennal responses in pollinating (Tegeticula) and non-pollinating (Prodoxus) moth species upon stimulation in electrophysiological recordings. In addition, synthetic (Z)-filamentolide attracted significant numbers of both sexes of two associated Prodoxus species in a field trapping experiment. Highly specialized insect-plant interactions, such as obligate pollination mutualisms, are predicted to be maintained through "private channels" dictated by specific compounds. The identification of novel bioactive tetranorsesquiterpenoids is a first step in testing such a hypothesis in the Yucca-yucca moth interaction.
Keywords: DMNT-derivatives; Floral scent; Pollinator attraction; Structure elucidation; Tetranorsesquiterpenoids; Total synthesis; Yucca